Interactive Digital Narratives as Complex Expressive Means - Bellini, Mattia (Frontiers in Virtual Reality, 2022)
The present article aims at discussing a complex-systemic understanding of the expressive mechanisms of Interactive Digital Narratives, to argue the expressive complexity of these artifacts. Interactors of Interactive Digital Narratives necessarily base their hermeneutic processes mainly on what is conveyed in the artifact itself; yet the question of how meaning is expressed in (and meaning-making is guided by) Interactive Digital Narratives remains significantly open. I contend that meaning expression in in such artifacts works by synthetizing the knowledge coming from a number of layers of information which are intercurrent, interdependent and interoperating, and which concurrently participate in the creation of an overall meaning of a higher order. According to complex systems theory, these layers are therefore elements of a complex system: this justifies my understanding of Interactive Digital Narratives as complex expressive means. Even though largely unexplored, this understanding of Interactive Digital Narratives as complex expressive means may help advance our knowledge of the representational capabilities and affordances of such products, not least in representing multifaceted worlds and complex phenomena. A complex-systemic view can foster our comprehension of the interpretative processes involved in the meaning-making of Interactive Digital Narratives. Furthermore, the awareness gained through this understanding could also be useful to get a better sense of the impact of the narratives featured in these artifacts, and ultimately to create more engaging and more powerful experiences that can help foster the societal impact of Interactive Digital Narratives.